FITNESS FOR SERVICE OF PIPING THAT HAS BRITTLE FRACTURE POTENTIAL - DEVAN FINANDO (NIM : 13107086); Dosen Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja, ARMENO
In oil and gas industry, equipments for transmition process consist of pipeline, truck and tanker.Pipeline is one of the most benefit equipment for the company. With greater time of use, and increase of operational load and temperature, pipeline equipments would reduce in terms of reliability and suffer functional failure, due to corrosion, geometrical defects, tears or cracks. To see the effects of reliability degradation, a Fitness For Service analysis is required. In this final project, the equipments are analyzed using the standards of API 579 part 3 level 1 and 2. This method consist of several complicated steps. A software, using Microsoft excel, is created to assist in calculations for each level. The case studied in this research is a piping in Tangguh Gas Station with the number of component 071-GL-1001-18”-3SAOK-CI that has a brittle fracture potention. From the data and information, it showed that this piping is operated in very low temperature that is -270.4F. The calculations for brittle fracture concern based on API 579 show that the piping doesn’t completed the acceptance criteria of level 1 and level 2, which means that the piping can’t continue to operate. This piping must be analized with further assessment that is level 3. Then analyze continued to indentify the parameters that influence integrity of component that has brittle fracture potention. That parameters is the governing thickness, material selection, range temperature, and acceptable criteria. This parameter influenced the value of MAT and the acceptable criteria for the piping component.